2017
DOI: 10.1080/01612840.2017.1278810
|View full text |Cite
|
Sign up to set email alerts
|

Can Completing a Mental Health Nursing Course Change Students' Attitudes?

Abstract: Nursing program graduates rarely choose mental health nursing as a career. A quasi-experimental study was conducted to examine attitudes of 310 nursing students towards persons with mental illness. Students completed surveys on the first and last days of their program's psychiatric mental health nursing course. The pre- and post-test survey analysis indicated that students improved their attitude, knowledge and preparedness to care for persons with mental illness. However, students maintained little interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…Study findings contribute nuance and depth to the current literature on students ' attitudes towards mental health nursing, which consistently demonstrates that students are disinterested in pursuing this area of nursing in their careers (Happell & Gaskin, ; Hastings et al, ; Hoekstra et al, ; Stevens et al, ). While the literature frequently positions students ' negative attitudes towards mental health nursing as a “lack of interest,” this study illuminates the importance of understanding how the context of the institutionalised mental health environment shapes students ' reflections on their future careers.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Study findings contribute nuance and depth to the current literature on students ' attitudes towards mental health nursing, which consistently demonstrates that students are disinterested in pursuing this area of nursing in their careers (Happell & Gaskin, ; Hastings et al, ; Hoekstra et al, ; Stevens et al, ). While the literature frequently positions students ' negative attitudes towards mental health nursing as a “lack of interest,” this study illuminates the importance of understanding how the context of the institutionalised mental health environment shapes students ' reflections on their future careers.…”
Section: Discussionmentioning
confidence: 60%
“…This finding challenges the dominant perspective in the literature that nursing students are not interested in a career in mental health nursing due to disinterest in working with the patient population because of stigma or fear of violence (e.g. Happell et al, ; Hastings et al, ). Additionally, this narrative offers a counterpoint to the literature suggesting that students are not prepared to work with individuals with mental health challenges following their practicums (Hunter et al, ; Walsh, ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The subscales requiring appropriate consideration and modification are as follows: knowledge of mental illness (KMI), anxiety surrounding mental illness (ASMI), negative stereotypes (NS) and beliefs on valuable nursing contributions to mental health (VC). Previous studies reported inadequate results for each subscale (Hastings et al, ; Hayman‐White & Happell, ). A study by Thongpriwan et al (), which adapted the scale to the U.S.A., is noteworthy in that it revealed adequate results for internal consistency for all subscales, except KMI and FC.…”
Section: Discussionmentioning
confidence: 90%
“…A study by Ewalds‐Kvist, Högbert, and Lützén () shows how students who had contact with real patients harboured more positive attitudes than those who had never faced real‐life clinical contexts. According to a range of authors, it has been demonstrated that clinical experience has a positive influence on the attitudes of nursing students towards patients with mental illness (Abuhammad, Hatamleh, Howard, & Ahmad, ; Happell, , Happell & Gough, ; Happell & Gaskin, ; Happell & Gough, ; Hastings et al, ).…”
Section: Discussionmentioning
confidence: 99%